The impact of N. Bonaparte expedition on Arab public consciousness - Қaбылхaновa, A.М. М.; Сaлқынбaев, М.Б. Б. (Journal of Oriental Studies, 2017)
The article is devoted to the study of the influence N.Bonaparte expedition to Egypt and Syria on the Arab public consciousness. This expedition takes an important place in the history, because N.Bonaparte campaign in 1798-1801 and the Western expansion influenced on the development of Arab public consciousness in new direction. The author describes from the historical point of view the French colonial expedition to Egypt and Syria. As well as, investigated Arab public consciousness, which formed on the basis of the bourgeois European culture.